NK cells from COVID-19 positive patients exhibit enhanced cytotoxic activity upon NKG2A and KIR2DL1 blockade - Lee, Grace; Schauner, Robert; Burke, Juanita; Borocz, Jade; Vasana, Smitha; Sobieraj, Lukasz; Giraudo, Maria; Jackson, Zachary; Ansari, Qasim; Navas, Maria; Sakr, Hany; Wald, David (Frontiers in Immunology, 2023)
SARS CoV-2 has caused a global pandemic leading to significant morbidity and mortality. There is a need to elucidate and further understand the implications of COVID-19 disease on the immune system to develop improved therapeutic strategies. In particular, Natural Killer (NK) cells play an essential role in mediating the innate immune response against viral infections. To better understand the role of innate immunity in COVID-19, we characterized the phenotype of circulating NK cells from 74 COVID-19 patients and 25 controls. Through evaluating the protein expression of activating and inhibitory NK cell surface molecules using dimension reduction analysis and clustering, we identified 4 specific clusters of NK cells specific to disease state (COVID-19 positive or COVID-19 negative) and characterized COVID-19 positive NK cells as: NGK2A+KIR2DL1+NKG2C-. Utilizing blocking antibodies specific for receptors NKG2A and KIR2DL1, we found that both NKG2A and KIR2DL1 blockade markedly enhances the ability of NK cells from COVID-19 positive patients to lyse SARS-Cov-2 infected cells. Overall, this study reveals new insights into NK cell phenotypes during SARS-CoV-2 infection and suggests a therapeutic approach worthy of further investigation to enhance NK cell-mediated responses against the virus.